Development of a 2D Educational Animation on the Adverse Health and Mental Effects of Excessive Gaming - Navelina, Navelina; Syahputra, Bayu (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
Online video games are one of the popular entertainment media among young people. However, it can increase the phenomenon of game addiction among students which has the potential to cause health and mental problems. This study aims to develop educational media in the form of 2D animated videos about the adverse health and mental effects of excessive gaming. The method used in this research is the Research and Development (R&D) approach with the Multimedia Development Life Cycle (MDLC) framework. Consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The final product is a 2–3-minute animated video published on social media platforms such as YouTube and Instagram Reels. Validation was conducted through assessments by 81 respondents (students/teenagers) as users. The results show that this 2D educational animation received an average score in the “very good” category in terms of visual appearance, narration, content, and overall appeal. Thus, the media is considered an effective and engaging digital learning tool for increasing student and youth awareness about the harmful effects of game addiction.